Managing Rust Disease in chickpea in transitional tract of Karnataka - PATIL, B. S.; Bhat, J. S. (Indian Farming, 2015)
Chickpea rust caused by Uromyces ciceri-arietini has not received much attention so far, as it appears late in the season when the crop is maturing. It has caused significant yield losses in chickpea growing in transitional tract of Karnataka in the previous 2-3 years. The disease first evidenced as small round or oval, light brown to dark brown pustules on both surfaces of foliage and in advanced stage gives brick red colour to whole plant, which could be identified from distance. Temperature is the key factor for both viability and germination of uredospore. There is no report of resistance source in cultivated species. Evaluation of wild relatives and creation of variability is essential.